Application of glucoamylase hydrolysis with anaerobically driven microbial fuel cells : Effect on energy generation from potato wastes - Siddique, Md Nurul Islam; Zaied, Khalid; Mohd Zamri, Ibrahim; Noraaini, Ali; Nazaitulshila, Rasit; Muhammad Syarifuddin, Yahya; Ghanem, Waheed Ali H.M. (Asian Publication Corporation, 2022)
A unique dual-phase biological system for producing power from the potato wastes was developed. In the beginning, commercially available glucoamylase was used to hydrolyze potato wastes resulting the production of potato waste hydrolyzate. A 100 g of potato waste produced 30 g of hydrolysis solid and 750 mL of potato waste hydrolyzate. Within 6 h, the maximum glucose generation was 20 g/L while the maximum COD elimination was 85%. During the second phase, the soluble potato waste hydrolyzate was utilized to feed microbial fuel cells (MFC), which produced electricity. The maximum voltage measured was 1.1 V. When the external resistance was 1091 Ω, the power density reached its greatest point of 93 mW/m3. To evaluate MFC performance, a Coulombic efficiency of 20% was obtained, thus exploring a new field by converting the high-starch molecules into biofuels, thereby lowering the cost of commercial biofuel production.